Management of cerebrospinal fluid leak: the importance of multidisciplinary approach - Galli, Jacopo (Acta Otorhinolaryngol Ital, 2021)
Cerebrospinal fluid (CSF) leak remains a rare condition, characterized by serious complications and potentially fatal. According to different etiologies, CSF leaks may be classified into two main categories: traumatic and spontaneous. Spontaneous fistulas seem to be mainly related to obesity and idiopathic intracranial hypertension. Diagnosis is both clinical and radiological. During the last three decades, surgical treatment has mostly shifted to endonasal endoscopic approach, which widely demonstrated to be more effective than invasive intracranial ones. Post-operative complications, long-term sequelae and hospital stay are strongly reduced thanks to endoscopic approach. The diagnosis and treatment of CSF leaks represent a difficult and challenge task. The main effort seems to be related to the precise localization of the leak. An accurate assessment of both predisposing factors and comorbidities is mandatory in case of spontaneous leaks. However, a clinical multidisciplinary evaluation as well as treatment, is essential to decrease the rate of failure of surgery. The presence of a dedicated instruments, the Skull Base Team, the knowledge of reconstructive materials and techniques represents a decisive result in therapeutical management even if for each patient an effective therapeutic algorithm can be obtained considering the correct leak detection and characteristics. In conclusion the strict teamwork with neurosurgeons, neuroradiologists, ophtalmologists will enable the development also of innovative biomaterials, which could spread and standardize multi-layer techniques, nowadays still related to surgeon preferences.